Chemical vapor deposition of bilayer graphene with layer-resolved growth through dynamic pressure control. Issue 31 (25th July 2016) - Luo, Birong; Chen, Bingyan; Wang, Anle; Geng, Dechao; Xu, Jie; Wang, Huaping; Zhang, Zhiyong; Peng, Lianmao; Xu, Zhiping; Yu, Gui
Abstract : Large-area AB stacked bilayer graphene layers with layer-resolved growth were successfully fabricated through dynamic pressure chemical vapor deposition. Abstract : In this work, a dynamic pressure atmosphere is constructed through cutting off the gas outlet in the chemical vapor deposition process, in which the total pressure of the system uniformly varies with a gradient and the associated growth environment changes. Through modulating the variation rate of system pressure, the layer-resolved growth of graphene from single-layer graphene grains to bilayer graphene patches and then ultimately larger-area bilayer graphene films has been realized. Based on the analysis results obtained, it is shown that the self-limiting effect of single-layer graphene on Cu foil can be broken by the accumulation of feedstock (CH4 /H2 ) during this dynamic process to enable the continued growth of bilayer graphene. The electrical transport studies demonstrate that devices made of the as-grown bilayer graphene exhibit obvious tunability of the band gap, showing the typical characteristics of AB stacked bilayer graphene.